The influence of social media usage and electronic word-of-mouth (eWOM) on purchase intention for local fashion products on Tiktok social media - Febyola, Annisa; Widyanesti, Sri (ARKA INSTITUTE, 2024)
This study investigates the influence of social media usage and electronic word-of-mouth (eWOM) on consumer purchase intentions for local fashion products on TikTok. Conducted among 385 TikTok users familiar with Indonesian fashion brands, the research employs Structural Equation Modeling (SEM) to analyze data. The results reveal significant positive relationships between social media engagement, eWOM, information quality, usefulness, information adoption, and purchase intention. Findings highlight the pivotal role of TikTok in enhancing brand equity through interactive content and direct consumer interaction. The study contributes insights into consumer behavior in the digital age, offering practical implications for businesses aiming to optimize marketing strategies on social media platforms.